3D printing and controlled release of functional ripening surimi improved by nano starch-xylo-oligosaccharides: Chemical bonds and microstructure influences. (October 2022) - Li, Gaoshang; Hu, Zhiheng; Zhan, Junqi; Huang, Jiayin; Lu, Zijing; Yuan, Chunhong; Chen, Jianchu; Hu, Yaqin
Abstract: To solve the problem of fast release, unsustainability of functional compounds in 3D printed surimi, nano scale of rice starch-xylo-oligosaccharides (XOS) was prepared. Meanwhile, its characteristics and printing effects on surimi were determined. Results shown that the nano rice starch and XOS with ratio of 1:2.5 had good characteristics (particle size 444 nm, embedding rate 86%, stable particle size with Na + and heating process). Moreover, it endowed surimi with antioxidant ability and prolonged the release of XOS in surimi during in vitro digestion, which might keep it for continuous release. Additionally, nano starch-XOS increased ionic bonds and hydrogen bonds by 78% and 58% respectively to enhance gel strength, texture of surimi. As well as it also could fill up gel network gaps to form denser structure, which increased self-supporting ability to improve printing effects. While excessive XOS (>1%) could wrap protein to inhibit gel formation to produce burs and pores of printed surimi-XOS, leading to the pores enlargement and collapse due to the enhancement of hydrophobic force and disulfide bonds after ripening. However, nano starch could aggregate XOS to delay the occurrence of collapse (>2% XOS content). Thus, nano starch-XOS could promote the application of functional surimi in 3D printing. Graphical abstract: Unlabelled Image Highlights: XOS release rate of surimi-nano starch-XOS under in vitro digestion were measured. Printed surimi with nano starch-XOS and their shapes after ripening were compared. Texture, gel strength, structure, chemical bond of printed surimi were determined. Influence mechanism of nano starch-XOS on printed surimi were analyzed.